What do we currently know about the development of talent? A systematic review in the soccer context - Verbeek, J.; Van Der Steen, S.; Van Yperen, N. W.; Den Hartigh, R. J. R. (International Review of Sport and Exercise Psychology, 2025)
Talent development is a key topic in sport psychology research and practice. To evaluate what we currently know about the development of talent, this systematic review used a two-dimensional taxonomy to classify contemporary talent research as (1) static or dynamic, and (2) inter- or intraindividual. We focused on empirical studies in the context of soccer, in which most of the talent research so far has been conducted. Following a literature search in July 2022 of Web of Science, Scopus, PsycINFO, and PubMed, 85 empirical studies were included. Most (n = 60) of the studies examined talent development from a static-interindividual perspective. These studies typically explored which factors explained future ability levels in groups of talented players. Only three studies explicitly examined how future ability emerged from interacting talent factors that changed over time for individual players, and were classified accordingly as dynamic-intraindividual. Hence, we conclude that most empirical studies on talent development in soccer lack data on individual temporal processes, which limits our current understanding of how talent develops. To move forward, we recommend that future studies in sports examine how talent development unfolds over time, considering the underlying dynamic and individual nature of this process.